Factors Determining Institutional Customer Decisions Regarding The Courier Service on The Polish Market - Marcin JANOWSKI (Communications of International Proceedings, 2021)
The article analyzes the behavior of institutional customers in relation to courier services provided in Poland. Rapid growth of e-commerce has stimulated changes in the provision of courier services, and customers have been offered a range of new opportunities and ways to send and receive mailings. These capabilities have changed the behavior of customers who look for more convenient and tailor-made offers. Since the perception of the courier operators has also changed, the author of the article considered it appropriate to present results of primary research on the Polish courier services market. This article refers to a research into a group of institutional customers and complements previous research on individual customers. The study provides a synthetic analysis of results and an attempt to interpret them in the light of the current courier market reality.
Keywords: Courier Services; Brand Perception; Customer Loyalty.